(untitled) (Wal’afiat Hospital Journal, 2021)
Background: Patient satisfaction is the first indicator of a hospital standard and a measure of service quality. Understanding the needs and desires of the patient is important that affects patient satisfaction, to help improve the quality of health services, requiring the establishment of Social Security administering Agency (BPJS) which is required to provide Satisfaction in patients. The services provided by the hospital must be qualified and meet the five dimensions of the main quality: tangibles, reliability, responsiveness, assurance, and Emphaty. Research aims: To determine the level of satisfaction of BPJS patients on the service of chemotherapy in Ibn Sina Makassar Hospital in June year 2019. Research methods: This research is a descriptive draft study using a cross sectional approach. The samples in this study were 54 people who meet the criteria for inclusion and exclusion. The data collection techniques used are questionnaire. Results of the study: according to the research results of BPJS patient satisfaction level of chemotherapy in the hospital Ibn Sina Makassar, using the dimensions obtained in the dimension tangible 50% satisfied and 50% very satisfied, on the reliability dimension 37 % were satisfied and 63% were very satisfied, on the dimension responsiveness 51.9% satisfied and 48.1% very satisfied, on the dimension of assurance 29.6% feel satisfied and 70.4% very satisfied, and on the dimension of Emphaty 38.9% feel satisfied and 61.1% feel very satisfied. Conclusion: The quality of service quality of tangible, reliability, responsiveness, assurance, and emphaty affects the level of patient satisfaction of the participants of the Social security health provider to the Ministry of Action chemotherapy at the hospital Ibn Sina Makassar.